2016
DOI: 10.3390/nu8120777
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Folate-Enriched Eggs as a Functional Food for Improving Folate Intake in Consumers

Abstract: Functional foods enriched with folate may be beneficial as a means of optimizing folate status in consumers. We recently developed novel eggs enriched with folate through folic acid supplementation of the hen’s feed, but their potential to influence consumer folate status is unknown because the natural folate forms incorporated into the eggs may not necessarily be retained during storage and cooking. This study aimed to determine the stability of natural folates in folate-enriched eggs under typical conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…The results obtained for organic eggs correspond well to the values presented for eggs of unknown origin by Soongsongkiat et al (117 µg/100 g) [42] and Yon et al [43] (114 µg/100 g). Organic eggs from our study showed folate levels (93.7-142.8) comparable those found in folate-enriched free-range eggs reported by Altic et al [21] (123.2 µg/100 g). These authors found the total folate content in un-enriched barn and un-enriched freerange eggs at the much lower levels, i.e., 41.4 and 65.6 µg/100 g, respectively, compared to our results for eggs from the same farming system.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The results obtained for organic eggs correspond well to the values presented for eggs of unknown origin by Soongsongkiat et al (117 µg/100 g) [42] and Yon et al [43] (114 µg/100 g). Organic eggs from our study showed folate levels (93.7-142.8) comparable those found in folate-enriched free-range eggs reported by Altic et al [21] (123.2 µg/100 g). These authors found the total folate content in un-enriched barn and un-enriched freerange eggs at the much lower levels, i.e., 41.4 and 65.6 µg/100 g, respectively, compared to our results for eggs from the same farming system.…”
Section: Resultssupporting
confidence: 90%
“…These authors found the total folate content in un-enriched barn and un-enriched free-range eggs at the much lower levels, i.e., 41.4 and 65.6 µg/100 g, respectively, compared to our results for eggs from the same farming system. The difference observed in folate content between eggs from these two rearing systems was explained by Altic et al [ 21 ] by the fact that free range hens have access to the fresh forage and this can provide an extra folate source to their daily feed. Barn hens are only fed with processed feed, probably low in folates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Continued advancements in nutrient-enriched eggs (for example, eggs high in α-linolenic acid and docosahexaenoic acid [ 44 ], folate [ 45 ], iodine [ 46 ], and some lipophilic antioxidants [ 47 ]) may appeal to some consumer segments. Yet the potential market for these specialty products is not well understood, and their production partly depends on the availability of specific poultry feed formulations and supply chain infrastructure, and is complicated by the recent downsizing of poultry flocks noted above.…”
Section: Discussionmentioning
confidence: 99%